Features of Progress and Treatment of Postprimary Refractory Glaucoma in a Patient with Progressive Mesodermal Iris Atrophy - A. D. Chuprov; L. I. Popova; V. I. Lapochkin; A. V. Lapochkin; D. V. Lapochkin; L. V. Demakova (Oftalʹmologiâ, 2016)
The problem of degenerative diseases of the vascular tract of the anterior eye`s segment is one of the insufficiently explored in ophthalmology. The relevance of the problem lies in the tactical difficulties in treatment of patients with atypical current secondary glaucoma, that develops as a result of degenerative changes of the eye`s anterior segment. First of all this refers to diseases combined by term thе iridocorneal endothelial syndrome. On the foot of the syndrome is the proliferation of pathologically altered corneal endothelium and its migration as a membrane on the trabecular area of the anterior chamber angle and anterior surface of the iris. This leads to development of secondary angle-closure glaucoma. Purpose. To optimize the approaches to the treatment of secondary decompensated refractory glaucoma on the basis of the clinical case analysis. Patient and methods. A case of bilateral progressivemezodermal atrophy of the iris and the cornea on 49 years old patient, who appealed to the Kirov clinical Ophthalmology hospital in February 2015 year with repeatedly operated decompensated refractory glaucoma. The local status of the patient included: thinning of the front layer of iris, sometimes up to full atrophy with non-through defects and deformation of the pupil, precipitates and spots on the endothelium of the cornea, the anterior peripheral adhesions, membrane-like tissue on the trabecula and the front surface of the iris, glaucoma excavation of the optic disc. Results and discussion. A rare form of corneal endothelial syndrome: essential progressive atrophy of mezodermal of the iris and the cornea has been diagnosed. Pharmacological correction of the intraocular pressure and original drainage surgery was performed. As a result, the patient’s IOP decreased from 38 mm to 16 mm Hg pressure. Conclusions.The unusual nature of secondary glaucoma, according with the progression of essential mezodermal atrophy of iris and cornea caused difficulties in diagnosing and treatment tactics. Correct diagnosis helped to choose the proper individual tactics of combined treatment that allowed to compensate glaucomatous process and save the visual functions for restore an active lifestyle of the patient.